PRESENTATION, STAGING AND DIAGNOSIS OF LYMPHOMA: A CLINICAL PERSPECTIVE - Hingorjo, Mozaffer Rahim; Syed, Sadiqa (Journal of Ayub Medical College Abbottabad, 2008)
Background: Due to lack of awareness among health professionals, lymphoma is often misdiagnosed. This study was done to evaluate the clinical features and histopathologic subtypes of lymphoma. Methods: Sixty diagnosed cases of lymphoma were selected (aged 12-65 years) from medical units of Civil Hospital Karachi, during 1993 to 1998. Clinical history, physical examination and basic laboratory investigations including imaging procedures were done in all the patients. The diagnosis of lymphoma was based on histology, following the International Working Formulation classification system. This included lymph node biopsy and in some cases, biopsy of the bone marrow. The Ann Arbor Staging Classification was used to classify the extent of disease. Results: Out of 60 cases of lymphoma, 81.6% (49 cases) were diagnosed as non-Hodgkin’s lymphoma and 18.3% (11 cases) as Hodgkin’s disease, with an overall male predominance. Both categories exhibited a bimodal age distribution. Lymphadenopathy was the commonest presenting features in both the types of lymphomas; however, patients with Hodgkin’s disease had a prominence of ’˜B’ symptoms, whereas abdominal signs and symptoms were more common in non-Hodgkin’s lymphoma. On histopathology, majority of non-Hodgkin’s lymphomas (91.8%) showed a diffuse pattern, while mixed cellularity was the commonest type seen in Hodgkin’s disease (81.8%). Conclusion: Non-Hodgkin’s lymphoma was 4 times more common than Hodgkin’s disease. The vast clinical spectrum of lymphoma sometimes delays its diagnosis, leading to its eventual presentation in late stages. A general awareness is hence required among the health professionals regarding its varied clinical presentations. Keywords: Non-Hodgkin’s lymphoma, Hodgkin’s disease, Lymphadenopathy, Hepatomegaly, Splenomegaly